Craniofacial development in patients of Tessier No.0 cleft with a bifid nose using 3D computed tomography - Wang, Xin; Wang, Huan; You, Jianjun; Zheng, Ruobing; Xu, Yihao; Fan, Fei (Frontiers in Pediatrics, 2022)
Objective Considerable studies have focused mainly on the facial deformity of Tessier No.0 cleft with a bifid nose, but the deformity of the skull is not well understood. Therefore, our study aimed to explore the evolution of cranial dysmorphology and the chronology of Tessier No.0 cleft with a bifid nose, by three-dimensional measurements. Methods Ninety-six non-surgical patients and computed tomographic scans were included (No.0 cleft with a bifid nose, n = 48; controls, n = 48) and divided into five age subgroups. Craniofacial cephalometric measurements were analyzed by Mimics software. Results The widening of nasal bone was the most remarkable and persistent from 2 years old appropriately. The overall cranial base length in patients compared with controls increased 11.8 percent (P＜0.01) on average. The middle and posterior cranial fossa increasing accounted for most of this change. The cranial base angles also showed increased obviously. By analyzing the linear of the nasopharynx and respiratory tract, it was found that its development did not affect respiration. Conclusions The cranial base deformity of Tessier No.0 cleft with a bifid nose consists of the whole skull base and particularly the middle and posterior cranial base length increase. At the same time, there may be late closure of the spheno-occipital synchondrosis and sella displacement. we believe this study is unique in providing valuable data for elucidating the pathological and morphological abnormalities of skull base development in Tessier No.0 cleft with a bifid nose.